Analysis of heavy metal content (Pb, Cu, Cd, and Fe) in the seagrass Thalassia hemprichii as a bioindicator of marine pollution in Tihi-Tihi Village, Bontang City, East Kalimantan - Safira Nurullita; Jailani , Jailani; Hamdhani , Hamdhani (Faculty of Fisheries and Marine Science, Mulawarman University, 2025)
The waters of Bontang City have relatively productive anthropogenic activities that trigger changes in the quality of surrounding waters that have the potential for pollution in the waters of the Bontang City area and there is a seagrass ecosystem that can be used as a natural indicator because it is sensitive to the presence of pollutants. To answer the problems found, this final project aims to determine the concentration levels of heavy metals (Pb, Cu, Cd, and Fe) contained in seagrass Thalassia hemprichii species in the waters of Tihi-Tihi Village. This study uses descriptive methods and location determination using the purposive sampling method and heavy metal analysis in water samples, sediments, and seagrass T. hemprichii analyzed using the AAS (Atomic Absorption Spectrophotometry) tool. The results showed that the waters of Tihi-Tihi Village had been contaminated with the heavy metal content of Pb, Cu, Cd, and Fe with different concentration levels, the metal content in water ranged from <0.001-0.098 mg/L, in sediment ranged from 2.64-1063.53 mg/kg and in seagrass ranged from 0.02-3468.08 mg/kg.